Q-switched fiber laser employing a passive polarization-maintaining thulium-doped fiber as a saturable absorber - Al-Alimi, A.w.; Mohd Yusoff, N.; Cholan, N.a.; Alresheedi, M.t.; Abas, A.f.; Talib, Z.a.; Mahdi, M.a. (Elsevier, 2021)
We present the application of polarization-maintaining thulium-doped fiber (PM-TDF) as a saturable absorber in an erbium-ytterbium-doped fiber laser. A commercial erbium-ytterbium-doped fiber amplifier (EYDFA) was employed in a ring cavity laser configuration with a sub-cavity that allowed bidirectional light propagation through PM-TDF. The Q-switched pulse operation was attained at 1563 nm with EYDFA output power of 720 – 980 mW. At maximum output power, the shortest pulse width of 1.4 µs was attained at 29.4 kHz repetition rate, with up to 41.7 mW of average output power and 1.44 µJ of pulse energy. The proposed fiber laser architecture demonstrated good stability in the time and frequency domains, thus recognizing its potential for applications that require high damage threshold saturable absorber devices.